Prevalence of Cardiovascular Disease Risk Factors Among Secondary School Pupils in Sulaimani City Kurdistan-Iraq. A Cross-Sectional Study - Qadir, Muhammed S.; M. Weli, Sardar (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Cardiovascular diseases (CVDs) are responsible for a high proportion of deaths caused by non-communicable diseases (NCDs) worldwide. The incidence of CVDs is largely attributed to several risk factors.Aim of the study: To estimate the prevalence of common risk factors of cardiovascular diseases among secondary school students in Sulaimani city / Kurdistan-Iraq.Subjects and Methods: One thousand and two hundred secondary school students between 16-18 years of age from eight secondary schools in the city of Sulaimani were selected to participate in this study. Students were selected randomly. The questionnaire form, which includes information about risk factors related to cardiovascular diseases, was filled by these students, after which, weight and height were measure to calculate the body mass index (BMI) in addition to measuring blood pressure (BP).   Permission to conduct the study was obtained from the principles of the participating schools. Consents were obtained from the parents of the students and the students themselves before data collection.Results: Low physical activity was very high among both males (84%) and females (95.8%). Although the rate of smoking was low among both males (12%) and females (4.2%), the association was statistically significant. The rate of smoking tobacco products other than cigarettes (water pipe and vape) was 27.6% among males and 10.2% among females. The rate of high systolic blood pressure was 6.7% and 2.9% in males and females respectively while the rate of high diastolic blood pressure was 5% and 10.7% in males and females respectively. The rates of high systolic blood pressure among overweight, normal weight and underweight students were 8.3%, 4.0% and 1.6% respectively.Conclusion: A significant prevalence of modifiable common risk factors such as low physical activity, smoking, hypertension, overweight and obesity were found among both male and female secondary school students in Sulaimani city.